Smart City as the Basic Construct of the Socio-economic Development of Territories - Shichiyakh, Rustem A.; Klyuchnikov, Denis A.; Balashova, Svetlana P.; Novoselov, Sergey N.; Novosyolova, Natalya N. (International Journal of Economics and Financial Issues, 2016)
The relevance of this topic is that any self-respecting city needs a development strategy that develops on the basis of the ideal representations of the future and opportunities. All of the city strive to achieve two fundamental goals. The first is to create a high-quality living environment, which is dictated by growing competition for investment and brains. The second objective - to ensure sustainable development, i.e. the search for the integrated (economic, social, transport, energy, environmental, etc.) model, which would guarantee a dignified existence for at least several generations of citizens. Currently in addressing the challenges of economic modernization and innovative development of Russia a key role to be played by information, knowledge, the widespread use of information and communication technologies, the problems of optimum use of natural resources and ecology, as well as the formation of the social environment, designed to provide optimal conditions for the work of participants the innovation process (Shkurkin, Shestopal, Gurieva, Blaginin and Gurianov 2016). In this context, the problem of creating smart cities is today one of the most pressing. Background of the idea of “smart” city and its development: increase in workload infrastructures. Keywords: Economic development, regional development, smart city, infrastructure, resources JEL Classifications: Ðž13, R13